Tuning Supramolecular Rigidity of Peptide Fibers through Molecular Structure - Pashuck, E. Thomas (2010)
We synthesized a series of peptide amphiphiles (PAs) with systematically modified amino acid sequences to control the mechanical properties of the nanofiber gels they form by self-assembly. By manipulating the number and position of valines and alanines in the peptide sequence we found that valines increase the stiffness of the gel while additional alanines decrease the mechanical properties. Vitreous ice cryo-transmission electron microscopy shows that all PA molecules investigated here form nanofibers 8–10 nm in diameter and several micrometers in length. We found through Fourier transform IR experiments a strong correlation between gel stiffness and hydrogen bond alignment along the long axis of the fiber. Molecules that form supramolecular structures with the highest mechanical stiffness were found by circular dichroism to self-assemble into β-sheets with the least amount of twisting and disorder, a result which is consistent with IR experiments. Molecular control of mechanical stiffness in three-dimensional artificial peptide amphiphile matrices offers a chemical strategy to control biological phenomena such as stem cell differentiation and cell morphology.